Karakteristik Kimia Dan Sensoris Biji Kakao Hasil Fermetasi Pada Tingkat Petani Dan Skala Laboratorium - Dome, Zulkifli SY.; Rahmatu, Rostiati Dg; Hutomo, Gatot Siswo (AGROTEKBIS, 2013)
Fermentation is a very vital stages of processing to ensure the production of a good chocolate flavor. The main purpose of this study to determine the chemical and sensory characteristics of fermented cocoa beans at the farm level and laboratory scale.  Fermentation methods do farmers with cocoa beans entering into fermnetasi box 50 kg and on the top of a banana leaf coated cocoa beans, then covered with a burlap sack with a rock ditindis. Further laboratory fermentation method by taking 5 kg of dry cocoa farmers who are not fermented cocoa plus 5 kg of wet samples, and then poured enough water until evenly distributed.  Fermentation box measuring 25x25 cm used for 5 days. During cocoa fermentation pengadukann every 48 hours the fermentation process running. Observations of temperature, pH and sampling was conducted every 6 hours fermentation, samples taken vriser stored in preparation for analysis of water content, protein content, soluble sugar content, and sensory properties. Temperature observations at the farm level rise slower than laboratory scale, where the maximum temperature reaches 45oC farmers (96 hours) and laboratory temperature of 45 ° C (33 hours). In the fermentation pH scale farmers and are relatively the same laboratory, where the pH optimum of 4.60 further 4.44 at the end of fermentation. Water content in the fermentation of farmers is higher than the laboratory-scale fermentation, where the initial fermentation reached 37.08% and 36.12% in laboratory scale, then the final moisture content of 29.29% farmers ferment and 27.85% in laboratory scale. Protein levels at the beginning of fermentation farmers are 4.78% and 5.13% laboratory scale, then the protein at the end of fermentation farmer 4.70% and 4.98% laboratory scale.  Sugar levels at the beginning of fermentation farmers as much as 15.54 mg / g and laboratory SKAL 15.34 mg / g, and at the end of the fermentation of sugar farmers be 8.86 mg/g and laboratory skla be 8.90 mg / g. Sensory test results using 16 panelists, where panelists really liked fermentation of cocoa beans in the roaster laboratory scale and alkalization.